ANTIHYPERTENSIVE EFFICACY OF VERAPAMIL PLUS INDAPAMIDE IN PATIENTS WITH METABOLIC SYNDROME - E. M. Idrisova; T. P. Kalashnikova; E. I. Mananko; E. V. Vorobyeva (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study effect of combination of verapamil retard (Isoptinum SR) with indapamide retard (Arifon retard) on blood pressure (BP) level as well as lipid profile, glucose and electrolytes serum level in patients with metabolic syndrome (MS).Material and methods. 20 women of 35-65 y.o. with MS were examined. The combination of verapamil retard and indapamide retard were prescribed to patients during 24 weeks. Ambulatory BP monitoring (ABPM), lipide profile tests, electrolytes and glucose serum level tests were performed in all patients initially and after treatment.Results. Target systolic BP (SBP) was achieved in 90% of patients. Target diastolic BP (DBP) was achieved in 75% of patients. Drug combination effectively reduced SBP, DBP and pulse BP levels and improved other BP indices. This drug combination did not affect BP profile as well as glucose and electrolytes serum level, lipid profile.Conclusion. High antihypertensive efficacy and metabolic neutrality of verapamil retard and indapamide retard allows to use this combination in patients with MS.